2003
DOI: 10.1007/s00335-003-2275-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of leptin gene polymorphisms with serum leptin concentration in dairy cows

Abstract: Leptin is a hormone produced by adipocytes, and its expression is regulated by body fatness and energy balance. This study describes the association of four leptin gene polymorphisms in dairy cows (R4C, A59V, RFLP1, and BM1500) with circulating leptin concentrations during the periparturient period. A59V is located at a between-species conserved region of leptin, and R4C might have effect on the tertiary structure of the leptin protein because of the presence of an extra cystein. RFLP1 is an intronic SNP and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
1
11

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 30 publications
6
60
1
11
Order By: Relevance
“…On the other hand, the observed negative effect on fat percentage could be simply a consequence of the higher milk yield without simultaneously increased amount of produced fat. The investigations on Dutch heifers (Liefers et al, 2003;Liefers, 2004) and British experimental population (Lagonigro et al, 2003) provided more arguments against the hypothesis postulated by Buchanan et al (2002). Liefers et al (2003) obtained results suggesting that not the TT, but the CC genotype is characterized by a higher circulating leptin concentration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the observed negative effect on fat percentage could be simply a consequence of the higher milk yield without simultaneously increased amount of produced fat. The investigations on Dutch heifers (Liefers et al, 2003;Liefers, 2004) and British experimental population (Lagonigro et al, 2003) provided more arguments against the hypothesis postulated by Buchanan et al (2002). Liefers et al (2003) obtained results suggesting that not the TT, but the CC genotype is characterized by a higher circulating leptin concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological properties, as well as the effects of the mouse ob locus variants support leptin as a strong candidate gene that could influence production traits in farm animals. In cattle, several studies have indicated an association between leptin gene polymorphisms and feed intake and carcass fat content, although reproduction and milk related traits were proved to be also affected (Fitzsimmons et al, 1998;Zwierzchowski et al, 2001;Liefers et al, 2002Liefers et al, , 2003. Buchanan et al (2002) proposed the C/T substitution in exon 2 that causes amino acid change from Arg to Cys at position 4 of the leptin protein (Arg4Cys) as a causative mutation affecting fat carcass content in cattle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Almeida et al 683 Many genetic and environmental factors influence reproductive performance and weight gain, with each individual gene having a small effect. As a matter of fact, mutations in other genes, mainly in leptin, are being described as affecting cattle weight gain and reproduction (Almeida et al, 2003(Almeida et al, , 2007Liefers et al, 2002Liefers et al, , 2003Liefers et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%